A Comprehensive Systematic Review of The Relationship Between Obesity and The Prevalence of Dyspepsia - Yuliana Sintia; Abilio Noviandi Jung (The Indonesian Journal of General Medicine, 2026)
Introduction: The parallel rise in global obesity rates and the prevalence of functional gastrointestinal disorders, particularly dyspepsia and gastroesophageal reflux disease (GERD), presents a significant public health challenge. Understanding the nature and strength of this association is crucial for effective clinical management and public health strategies (Eslick, 2012; Mahadeva, 2023). Methods: A comprehensive review was conducted by screening studies from multiple databases. Studies were included if they investigated the obesity-dyspepsia association as a primary objective, used validated measures for both obesity (e.g., BMI, waist circumference) and dyspepsia (e.g., Rome criteria, clinical diagnosis), involved adult populations, and reported quantitative data. Data on study characteristics, obesity measures, dyspepsia definitions, population demographics, association findings, proposed mechanisms, and limitations were systematically extracted from 59 included sources. Results: The evidence demonstrates a consistent positive association between obesity—particularly central adiposity—and dyspepsia/GERD. Meta-analyses show overweight individuals (BMI 25-30 kg/m²) have an odds ratio (OR) of 1.43-1.60 for GERD, rising to 1.94-2.15 for those with obesity (BMI >30 kg/m²) (Hampel, Abraham, & El‐Serag, 2005; Corley & Kubo, 2006; Cai et al., 2012). Central obesity measures like waist circumference show even stronger correlations (Zhan et al., 2021). However, findings are heterogeneous, with associations attenuated when controlling for diet and physical activity (Levy et al., 2005), and weaker or absent in some ethnic groups, particularly Asian populations (Goh, 2007). Discussion: The relationship is mediated by multiple interconnected pathophysiological mechanisms, including mechanical effects (increased intra-abdominal pressure, lower esophageal sphincter dysfunction), inflammatory pathways, hormonal alterations, and visceral hypersensitivity (Mathus-Vliegen & Tytgat, 2002; Al Mushref & Srinivasan, 2013; Doerfler et al., 2020). Weight loss of at least 10% significantly improves symptoms and reduces medication need (de Bortoli et al., 2016), while proton pump inhibitor (PPI) efficacy appears unaffected by BMI (Sharma et al., 2013; Peura et al., 2011). Conclusion: Obesity, especially central adiposity, is a significant modifiable risk factor for dyspepsia and GERD. Clinical management should prioritize weight loss and waist circumference measurement alongside conventional therapy. Future research should focus on ethnic-specific mechanisms and the role of lifestyle confounders.